THE RELEVANCE OF USHUL FIQH IN THE METHOD OF LEGAL CHANGE EFFECTIVENESS OF ROAD TRAFFIC AND TRANSPORT ACTS - Sudirman Suparmin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
The problem of traffic violations in Indonesia with a percentage of 44.89%, is a problem of mutual concern. Of course, this needs to be studied explicitly so that a solution to the problem is found. This problem is in line with the concept of the ushul fiqh method in changing the law. This study aims to determine the relevance of Ushul Fikih in changing the law on the needs of the traffic community and to find out the traffic law responds to traffic violators. The legal research method used in this research is a type of normative legal research with a statute aproch approach or a statutory approach and looking at the method of legal change in ushul fiqh. The results of the research on the Relevance of Ushul Fikih in the Method of Legal Change for the needs of the cross-sectional community are very much in line with this method considering that the consideration is the benefit of the human ummah in traffic, then the traffic law responding to traffic violators is indeed seen in the study Academic manuscripts have become the subject of study in the legislature to make laws that are in accordance with the needs of the community in traffic.